2016
DOI: 10.1089/jmf.2016.3706
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Marine Algal Polyphenolic Compounds: A Mechanistic Approach

Abstract: Polyphenolic compounds isolated from marine algae exhibit a broad spectrum of beneficial biological properties, including antioxidant, anticancer, antimicrobial, anti-inflammatory, and antidiabetic activities, along with several other bioactivities centered on their antioxidant properties. Consequently, polyphenolic compounds are increasingly being investigated for their potential use in food, cosmetic, and pharmaceutical applications. The antioxidant activities of these compounds have been explored widely thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(106 citation statements)
references
References 128 publications
(134 reference statements)
3
97
0
6
Order By: Relevance
“…A number of studies have investigated the antioxidant properties of flavonoids in terms of anionic superoxide scavenging (104,105). The antioxidant potential of Asparagopsis taxiformis extracts indicates that algae extracts exert cytoprotective effects and supports their use as to treat conditions induced by oxidant stress.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have investigated the antioxidant properties of flavonoids in terms of anionic superoxide scavenging (104,105). The antioxidant potential of Asparagopsis taxiformis extracts indicates that algae extracts exert cytoprotective effects and supports their use as to treat conditions induced by oxidant stress.…”
Section: Discussionmentioning
confidence: 99%
“…Marine algae are a rich source of bioactive secondary metabolites, including phenols and polyphenols (Fernando et al 2016). Antioxidant activity, an important property of bioactive algal compounds, has been ascribed to their reactive oxygen species scavenging ability, quenching singlet oxygen, reducing power, and chelating ability (Andrade et al 2013;Maharana et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found that polyphenols in brown macroalgae have extraordinary and effective antioxidant activities (Zubia et al 2009;Machu et al 2015), which suggest that higher total phenolic content can result in higher antioxidant capacity. The high phenolic content of Baja California E. arborea, P. concrecens, and C. osmundacea can explain their potent radical scavenging activity, since polyphenol compounds contain reducing properties, such as hydrogen or electrondonating agents, which contribute to free radical scavenger potential (Fernando et al 2016). Although Acanthophora spicifera had low phenolic content, its extract had significant antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the total phenolic compound content obtained in sea spaghetti was significantly higher than in the rest of the species and this seaweed had the highest value of antioxidant activity measured by the ferric reducing antioxidant power (FRAP) and the 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) methods. In 2016, Fernando et al [27] reviewed the antioxidant properties of numerous polyphenolic compounds derived from marine algae and described their structure–activity relationship. The antioxidant effect of polyphenols is related to their capacity to enhance the enzymatic activity of different enzymes, including catalase, glutathione peroxidase and superoxide dismutase, their potent free radical scavenging properties and their ability to interact with other molecular targets, as they are capable of reducing arginase-2, and activating the Nrf2/ARE pathway and SIRT-1 [28] (Figure 2).…”
Section: Oxidative Stressmentioning
confidence: 99%